Conservative treatment of severe clubfoot using a novel functional dynamic splint. Issue 1 (January 2015) - Adachi, Nobuo; Fukuhara, Kohei; Nakasa, Tomoyuki; Shibuya, Hayatoshi; Okuhara, Atsushi; Kato, Tomohiro; Ochi, Mitsuo
Abstract : Forty-six severe clubfeet in 29 patients were treated by serial castings, followed by a newly developed dynamic splint. The mean period of splint usage was 59.9 months and the mean period of follow-up was 81.5 months. Of the patients, 76.1% were satisfied, 87.0% had no functional deficit, and 84.8% had no pain. Radiographical evaluation showed good correction. The mean dorsiflexion angle was –0.8° at the end of cast treatment and 13.6° at the time of the final follow-up. This study clearly showed the effectiveness of a functional dynamic splint for the correction of equinus in cases of severe clubfoot.